Sorptivity of water in sound and demineralised enamel / Gan Siew Chen - Gan, Siew Chen (2019)
Initial caries which present clinically as white spot lesions typically start with demineralisation of the enamel surface which causes an increase in surface porosity. At the same time, non-porous highly mineralised surface layer which is commonly known as “surface layer” progressively forms on the enamel. If demineralisation continues, the surface layer breaks down and the enamel surface becomes porous again. The intermittent presence of the surface layer in the cycle of remineralisation and demineralisation could be the reason for the lack of conclusive evidence of success in remineralisation therapies. Remineralisation materials may not be penetrating the surface efficiently when the surface layer is present. There are currently no clinical methods to determine the porosity of the enamel surface. If porosity and presence of the highly mineralised surface layer on white spot lesions can be determined, the success of remineralisation therapy can be improved. In this research, it is hypothesised that the measured rate of absorption using sorptivity on sound and demineralised enamel surface can be used to determine the level of porosity and presence of a surface layer on the enamel surface. The aim of this thesis is to determine the association between sorptivity of water and the state of mineralisation of surface enamel by first, exploring the viability of sorptivity as a tool to measure surface absorption rate on sound and demineralised enamel. Secondly, is to explore the associations between sorptivity with mineral density on sound and demineralised enamel surface. A 0.7 microliter droplet of water was placed with a micropipette on the exposed enamel of 96 teeth (192 test sites) which had undergone various duration of pH cycling (GS- group of specimens that did not undergo pH cycling, G7- group of specimens that underwent 7 days pH cycling, G14- group of specimens that underwent 14 days pH cycling, G21- group of specimens that underwent 21 days pH cycling, G28- group of specimens that underwent 28 days pH cycling and G35- group of specimens that iv underwent 35 days pH cycling). Thorlabs Swept-Source OCT system (OCS 1300SS) was used to measure the height of the drop every 10 seconds for 2 minutes. Sorptivity of each test site was then computed after accounting for evaporation. Total Delta Z of grey scale value from 10µm (TDZ10) to 50µm (TDZ50) was calculated using images taken with microcomputed tomography (Micro- CT). Integrated reflectivity is measured from 10 µm (IR10) to 50 µm (IR500 using images taken with OCT1300SS. SEM, Micro-CT, photography and stereo microscope images were taken to provide qualitative analysis. SPSS 25 (IBM) with One-way ANOVA, post-hoc Tukey and Dunnett’s T3 was used to compare means and Bivariate (Pearson) Correlations was used to compare 2 variables. Results show that mean sorptivity increased from GS to G14 and from G21 to G35, juxtaposed by a decline between G14 and G21. One-Way ANOVA showed significant difference of mean sorptivity between groups (p<0.0). Mean TDZ10 and mean IR10 seem to project the same relationship between groups. This appears to confirm the cycle of remineralisation and demineralisation and the presence of a surface layer in G21. The most significant correlation was found between sorptivity and TDZ10 with Pearson Correlation coefficient of 0.461. IR10 show significant correlations with sorptivity when results from GS, G7, G14 and G21 were chosen with Pearson correlation coefficient of 0.275. Qualitatively, the presence of a surface layer in many test sites in G21 explains the reason for low mean sorptivity value for this group. In conclusion, these tests have shown for the first time that sorptivity of water is linearly and inversely correlated with the state of mineralisation at the surface of enamel. Sorptivity can be used to determine the presence of a surface layer.